Early in-hospital management of cardiac arrest from neurological cause: Diagnostic pitfalls and treatment issues. (November 2018) - Legriel, Stephane; Bougouin, Wulfran; Chocron, Richard; Beganton, Frankie; Lamhaut, Lionel; Aissaoui, Nadia; Deye, Nicolas; Jost, Daniel; Mekontso-Dessap, Armand; Vieillard-Baron, Antoine; Marijon, Eloi; Jouven, Xavier; et al.
Abstract: Purpose: To explore diagnostic pitfalls and treatment issues in out-of-hospital cardiac arrest of neurological cause (OHCA-NC). Methods: Retrospective analysis of all consecutive patients from the Paris Sudden Death Expertise Centre (France) registry from May 2011 to September 2015 presenting with a sustained return of spontaneous circulation (ROSC) at hospital admission and a final diagnosis of OHCA-NC. Description of the early diagnostic check-up performed to identify the cause of cardiac arrest. Logistic multivariate regression to identify factors associated with immediate coronary angiography (iCAG) in OHCA-NC patients. Results: Among 3542 patients with ROSC, a final diagnosis of OHCA-NC was established in 247 (7%). The early diagnostic check-up consisted in a total of 207 (84%) immediate cranial CT-scan, 66 (27%) iCAG and 25 (10%) chest CT-scan. The brain CT-scan allowed identifying a neurovascular cause in 116 (47%) patients. An iCAG was performed as the first line exam in 57 (23%) patients, in whom a final diagnosis of neurovascular cause for OHCA-NC was later identified in 41 patients. By multivariate analysis, decision for iCAG was independently associated with ST-segment elevation on post-ROSC electrocardiogram (OR, 5.94; 95%CI, 2.14–18.28; P = 0.0009), whereas an obvious cause of cardiac arrest on scene was negatively associated with iCAG (OR, 0.14; 95%CI, 0.02–0.51; P = 0.01). Conclusions: OHCA-NC is a rare event that is mainly related to neurovascular causes. The initial ECG pattern may be a confounder regarding triage for early diagnostic check-up. Further studies are required to explore the potential harmfulness associated with decision to perform an iCAG in this population.